Learning Model Development of Disaster Mitigation for Elementary School Students at Lombok, Indonesia - Taufik, M.Si, Muhammad; Sutrio, Sutrio; Gunada, I Wayan; Syahrial A, Syahrial A; Doyan, Aris; Susilawati, Susilawati (Journal of Science and Science Education, 2024)
A research study conducted in Lombok Island, Indonesia, developed a learning model for disaster mitigation for elementary school students. The model is based on a scientific approach and incorporates knowledge about natural disasters, their causes, and effects. Students are taught how to identify and respond to warning signs of a disaster, and the importance of being prepared for one. The study found that the learning model was effective in increasing students' knowledge, skills, and attitudes about disaster mitigation. Students who participated in the study were better able to identify the warning signs of a disaster and take appropriate action, as well as express a greater sense of preparedness for a disaster. The learning model can be used to educate elementary school students about disaster mitigation in other regions prone to natural disasters. Teachers can use various resources to teach students about natural disasters, provide opportunities for practice identifying warning signs and responding to disasters through role-playing exercises, and help students develop a sense of preparedness by discussing the importance of having a disaster plan and practicing what to do in the event of a disaster. By incorporating the learning model into their curriculum, teachers can ensure that their students are prepared to face the challenges of natural disasters